Lifetime editions of I. L. Lypa’s works in the collections of the Scientific Library of the Odessa I. I. Mechnikov National University. - Velykodna, Ganna (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2025)
Goal. The article aims to study the lifetime editions of Ivan Lypa’s works kept in the collection of the Scientific Library of the Odessa I. I. Mechnikov National University as well as to analyze their significance for Ukrainian literature and the author’s social and cultural activities. The role of these editions in the formation of national consciousness and their influence on the development of Ukrainian book publishing is determined. Research methodology. The study applied general scientific approaches, the method of historiographic analysis and synthesis as well as basic methods of historical research. Scientific novelty. Lifetime editions of Ivan Lypa’s works from the holdings of the Scientific Library of the Odessa I. I. Mechnikov National University were studied for the first time, as part of a special bibliographic study. Special attention is paid to valuable provenance, thanks to which the history of each copy can be traced. Conclusions. I. Lypa’s works and activities became an important stage in the development of Ukrainian culture and national consciousness. His oeuvres reveal moral, social and national themes, actively contributing to the popularization of Ukrainian literature. Lypa’s publications during his lifetime are important sources for studying national revival, and his struggle for freedom and justice had a great influence on patriotic education. The Scientific Library of the Odessa I. I. Mechnikov National University acquired copies of his works during different stages of its development, which confirms their significance in the cultural and scientific context. Ivan Lypa’s heritage continues to inspire awareness of Ukrainian identity.